2020
DOI: 10.1002/dvdy.183
|View full text |Cite
|
Sign up to set email alerts
|

Spliceosomopathies and neurocristopathies: Two sides of the same coin?

Abstract: Mutations in core components of the spliceosome are responsible for a group of syndromes collectively known as spliceosomopathies. Patients exhibit microcephaly, micrognathia, malar hypoplasia, external ear anomalies, eye anomalies, psychomotor delay, intellectual disability, limb, and heart defects. Craniofacial malformations in these patients are predominantly found in neural crest cells‐derived structures of the face and head. Mutations in eight genes SNRPB, RNU4ATAC, SF3B4, PUF60, EFTUD2, TXNL4, EIF4A3, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 136 publications
2
52
0
Order By: Relevance
“…It has become clear that alternative splicing in different tissues is regulated by coordinated networks of splicing regulators (Ule and Blencowe, 2019). The importance of alternative splicing in craniofacial development is demonstrated by the observation that abnormalities in spliceosome or splicing regulators occur in several human birth defects often involving the craniofacial complex (Bain et al, 2016;Marques et al, 2016;Loiselle and Sutherland, 2018;Berube-Simard and Pilon, 2019;Beauchamp et al, 2020;Griffin and Saint-Jeannet, 2020). Two splicing regulators involved in promoting differential splicing in the ectoderm -Esrp1/2 -are known to cause mouse orofacial clefting of the lip and palate when deleted (Warzecha et al, 2009;Bebee et al, 2015;Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has become clear that alternative splicing in different tissues is regulated by coordinated networks of splicing regulators (Ule and Blencowe, 2019). The importance of alternative splicing in craniofacial development is demonstrated by the observation that abnormalities in spliceosome or splicing regulators occur in several human birth defects often involving the craniofacial complex (Bain et al, 2016;Marques et al, 2016;Loiselle and Sutherland, 2018;Berube-Simard and Pilon, 2019;Beauchamp et al, 2020;Griffin and Saint-Jeannet, 2020). Two splicing regulators involved in promoting differential splicing in the ectoderm -Esrp1/2 -are known to cause mouse orofacial clefting of the lip and palate when deleted (Warzecha et al, 2009;Bebee et al, 2015;Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with MFDM exhibit a variety of clinical findings and the most common are craniofacial defects such as microcephaly, developmental delay, mandibular and malar hypoplasia as well as external ear anomalies. In addition, as no correlation is found between patient`s genotypes and their clinical characteristics, these mutations are predicted to be loss-of-function mutations and suggest that the developing craniofacial region is more sensitive to reduced levels of EFTUD2 when compared to other embryonic cell types (reviewed in (Beauchamp et al, 2020)). Here, we report that altered splicing caused by the loss of Eftud2 results in the reduced inclusion of exon 3 of Mdm2 and nuclear accumulation of P53 in the neural crest cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, homozygous Eftud2 (Eftud2 -/-) mutant blastocysts failed to implant, precluding analysis of the role of Eftud2 during craniofacial development. These and other past studies confirmed that Eftud2 is an essential gene, but its role in neural crest cells, the precursors of bones and cartilages affected in the head and face of MFDM patients, has not been examined (Beauchamp et al, 2020;Deml et al, 2015;Lei et al, 2017;Wu et al, 2019). Therefore, we have generated a conditional Eftud2 knock-out mouse (Eftud2 loxP/+ ) in which exon 2 is flanked by loxP sequences to study the role of Eftud2 during craniofacial development.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…BMKS is one of five developmental craniofacial disorders caused by variants in core spliceosome components [6,17]. Given the universality of pre-mRNA splicing in the processing of all human pre-mRNAs, the very specific and tissue-restricted craniofacial phenotypes of these disorders are remarkable.…”
Section: Introductionmentioning
confidence: 99%